UPAYA PENINGKATAN KEMAMPUAN KEGIATAN PEMBELAJARAN MELALUI SUPERVISI AKADEMIK BAGI GURU SEKOLAH DASAR NEGERI NOMOR 14/II PASAR RANTAU EMBACANG - Pudyastuti, Heni (STKIP YPM Bangko, 2019)
This study purfose to see how efforts to improve the ability of learning activities through academic supervision of six teachers of Public Elementary School No. 14 / II Rantau Embacang Market, Tanah Sepenggal District. This research is a field research that applies a qualitative descriptive approach. The procedures in this study are carried out in the form of four stages: planning, action, observation and reflection. The results showed that there was an increase in teacher behavior from cycle 1 to cycle 2. Furthermore, the results of the study showed an increase in evaluation through the APKG cycle 1 instrument with a value of 3, 33 (three point thirty three) to 3.56 (three point fifty six) in cycle 2.